Pengaruh Pengungkapan Sustainability Reporting Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Daris Aviceena; Rahmat Hidayat; Reksa Arya Wardhana; Yane Devi Anna (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of sustainability reporting disclosure on firm value, with firm size as a moderating variable. The sample in this study consists of 20 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, selected using a purposive sampling method. Data analysis was conducted using moderated regression analysis within a panel data regression framework. The results show that sustainability reporting disclosure has a significant negative effect on firm value. Furthermore, firm size is found to positively moderate the relationship between sustainability reporting disclosure and firm value, indicating that larger firms are able to mitigate the negative effect of sustainability reporting disclosure on firm value.